2015
DOI: 10.2527/jas.2014-6971
|View full text |Cite
|
Sign up to set email alerts
|

The impact of dietary protein levels on nutrient digestibility and water and nitrogen balances in eventing horses1

Abstract: This study was performed to evaluate the impact of dietary protein levels on nutrient digestibility and water and nitrogen balances in conditioning eventing horses. Twenty-four Brazilian Sport Horses, male and female (8.0 to 15.0 yr; 488 ± 32 kg BW), were used in a randomized design with 4 levels of CP diets: 7.5%, 9.0%, 11.0%, and 13.0%. A digestion assay was performed with partial feces collection over 4 d, followed by 1 d of total urine collection. Data were submitted to regression analysis and adjusted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, soya groat-supplementation produced less faecal N, but not less urinary N, than in the other supplementations. Oliveira et al [ 59 ] found that soya digested well, but extra N was excreted in urine. Many studies reported elevated N lost in urine when the CP content in the feeds and CP intake was increased [ 41 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, soya groat-supplementation produced less faecal N, but not less urinary N, than in the other supplementations. Oliveira et al [ 59 ] found that soya digested well, but extra N was excreted in urine. Many studies reported elevated N lost in urine when the CP content in the feeds and CP intake was increased [ 41 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al [ 59 ] found that soya digested well, but extra N was excreted in urine. Many studies reported elevated N lost in urine when the CP content in the feeds and CP intake was increased [ 41 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, providing pelleted or steam-flaked barley instead of ground barley appeared to limit the negative impact of starch on fibre digestibility [35,39], and gradually increasing the amount of grain fed will have facilitated adaptation, enabling more pre-caecal starch digestion. Protein levels in the two high-energy diets were similar, and also greater than the control diet, and this may have been a factor contributing to the improved digestibility of NDF [40].…”
Section: Discussionmentioning
confidence: 89%
“…Animals on the hypercaloric diets showed significantly greater apparent digestibility of gross energy and crude protein, which may have been a consequence of the calories rather than other factors. However, the increased amount of protein-rich soya hulls and lucerne chaff in those diet groups might have contributed also, because increased dietary protein levels have been suggested to improve the digestibility of crude protein, NDF and ADF in sport horses [40].…”
Section: Discussionmentioning
confidence: 99%
“…Aguerre et al [ 39 ] and Lee et al [ 40 ] did not find an effect of diets ranging from 15.3% to 16.6% and 14.8% to 16.7% CP on DMI in dairy cows, respectively. Oliveira et al [ 41 ] also reported that DMI was unaffected by dietary CP levels in horses. In the present study, we observed no difference in DMI between the dietary protein levels, which might be caused by the isoenergetic diets.…”
Section: Discussionmentioning
confidence: 99%